2010 Cost Estimates of Establishing and Producing Pitaya (Dragon Fruit) in South Florida - Edward A. Evans; Jordan Huntley; Jonathan Crane; Allen F. Wysocki (EDIS, 2011)
FE888, a 7-page fact sheet by Edward A. Evans, Jordan Huntley, Jonathan Crane, and Allen F. Wysocki, provides needed information on the costs and returns associated with establishing and operating a five-acre pitaya orchard in South Florida, and assesses the prices and yields that must be obtained to make the establishment and production of a pitaya orchard a profitable venture. Published by the UF Department of Food and Resource Economics, December 2010.